EFFECT OF PURITY LEVEL OF CO2 SHIELDING ON METAL ACTIVE GAS WELDED JOINT QUALITY - Sawrav, Kumar; Bandyopadhyay, Partha Pratim; Das, Rajib (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The investigation deals with the study of the effect of the purity level of carbon dioxide shielding gas on the metal active gas weld quality. Studied 99.78 %, 99.95 %, and 99.97 % purity levels of carbon dioxide shielding gas. Factors considered were related to shielding gas purity, moisture, Sulphur, and oxygen content. Welded samples were subjected to ultrasonic testing to assess weld quality. With the reduction in purity level below 99.9 %, it was observed that the weld defect percentage increased in both lab trials and mass manufacturing jobs. The defects recorded were 5% higher when jobs were welded using carbon dioxide supplied from a gas cylinder than that supplied from liquid cryogenic bullets; this established that a higher purity level could be maintained in cryogenic storage and transport of shielding gases. This states helpful references to manufacturing industries for selecting the purity level of shielding gas, with the objective of rework reduction.